Extracellular Signal-regulated Kinase (ERK) Activation Is Required for GP Ibα-dependent Endothelial Cell Migration - Lian, Jie; Marcinkiewicz, Cezary; Niewiarowski, Stefan; Beacham, Dorothy A. (Thrombosis and Haemostasis, 2001)
The GP Ib complex can participate in endothelial cell (EC) migration on von Willebrand factor (vWF) or the mixed matrix of vWF and type I collagen (vWF/collagen). In this study, viper venom proteins alboaggregin (albo) A or B blocked GP Ibα, and echistatin inhibited αvβ3 binding. Albo A, B and echistatin inhibited EC migration on vWF and vWF/collagen. Albo B or the anti-GP Ibα monoclonal antibody (mAb) 1b1 did not affect the migration of smooth muscle cells or fibroblasts, which lack GP Ib. EC also migrate on albo A- or albo B-coated dishes. PD98059, which blocks ERK activation, abolished EC migration on vWF, vWF/collagen, collagen or albo B. Soluble albo A or 1b1 dramatically inhibited ERK activation during EC migration on vWF or albo B. Echistatin inhibited ERK activation on vWF and vitronectin (VN), but not albo B. Thus, in addition to αvβ3, EC GP Ibα initiates ERK activation, and regulates ERK-induced EC migration on vWF.
Keywords: Endothelial cell; migration; extracellular signal-regulated kinase; snake venom